The scars of youth: Effects of early-career unemployment on future unemployment experience - Achim Schmillen; Matthias Umkehrer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
Does early-career unemployment cause future unemployment? We answer this question with German administrative matched employer-employee data that track more than 800,000 individuals over 24 years. Using a censored quantile instrumental variable estimator and instrumenting early-career unemployment with local labor market conditions at labor market entry and firm-specific labor demand shocks, we find significant and longlasting scarring effects. At the median, an additional day of unemployment during the first eight years on the labor market increases unemployment in the following 16 years by 0.96 days. Effects are even stronger in the right tail of the unemployment distribution. Likely due to unobserved heterogeneity in returns to search, they are also understated by non-IV estimates. – – Steht Jugendarbeitslosigkeit in einem kausalen Zusammenhang mit der Erfahrung späterer Arbeitslosigkeit? Wir beantworten diese Frage mit Hilfe administrativer Integrierter Betriebs- und Personendaten, welche es uns erlauben, mehr als 800.000 Personen über 24 Jahre hinweg zu folgen. Indem wir Jugendarbeitslosigkeit durch zum Zeitpunkt des Arbeitsmarkteintritts vorherrschende regionale Arbeitsmarktbedingungen und firmenspezifische Arbeitsnachfrageschocks instrumentieren und Zensierte-Instrumentvariablen-Quantilsregressionen heranziehen, zeigen wir, dass Jugendarbeitslosigkeit signifikante und lang anhaltende Scarring-Effekte nach sich zieht. Im Median führt ein zusätzlicher Tag Jugendarbeitslosigkeit zu 0,96 weiteren Tagen Arbeitslosigkeit während der späteren Erwerbsphase. Im oberen Bereich der Arbeitslosigkeitsverteilung sind die Effekte noch ausgeprägter.
Keywords: J64; J62; C20; 330; Scarring; state dependence; censored quantile instrumental variable regressions; Scarring; state dependence; censored quantile instrumental variable regressions